2011
DOI: 10.1136/bmjqs-2011-000421
|View full text |Cite
|
Sign up to set email alerts
|

Time to accelerate integration of human factors and ergonomics in patient safety: Table 1

Abstract: Progress toward improving patient safety has been slow despite engagement of the health care community in improvement efforts. A potential reason for this sluggish pace is the inadequate integration of human factors and ergonomics principles and methods in these efforts. Patient safety problems are complex and rarely caused by one factor or component of a work system. Thus, health care would benefit from human factors and ergonomics evaluations to systematically identify the problems, prioritize the right ones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
143
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(145 citation statements)
references
References 20 publications
0
143
0
2
Order By: Relevance
“…Over the past decade, human factors design has been increasingly recognized as a tool for optimizing healthcare, particularly in the field of patient safety and infection prevention. [11][12][13][14][15][16][17][18] The concept of mental models is an important design tool for human factors engineers.…”
Section: Mental Models At the Core Of Human Factors Design In Healthcarementioning
confidence: 99%
“…Over the past decade, human factors design has been increasingly recognized as a tool for optimizing healthcare, particularly in the field of patient safety and infection prevention. [11][12][13][14][15][16][17][18] The concept of mental models is an important design tool for human factors engineers.…”
Section: Mental Models At the Core Of Human Factors Design In Healthcarementioning
confidence: 99%
“…The technology should be adapted to the people who use it, rather than expecting people to adapt to the technology. Such an approach is grounded in human factors, a field that is making contributions in the area of patient safety, 4 and that could also play a larger role in the area of health information technology. 5 …”
mentioning
confidence: 99%
“…Despite this there remains a gap between the medical field and other high-risk industries in the integration of HFE methods into healthcare practice [11,12,21]. This may in part be due to the fact that health professionals, without expertise or support of experts on HFE, are often asked to explore the usefulness of devices and/or to prevent and report device induced adverse events in the field [22].…”
Section: Introductionmentioning
confidence: 99%
“…Gurses et al [11] identified that healthcare professionals and researchers are not fully aware of the methods and principles of human factors and ergonomics (HFE). HFE is the multidisciplinary science in which human behaviour, capacities and engineering principles are used to explore why errors occur, and how to reduce the likelihood of preventable harm to individuals, with the specific aim to support human performance and safety [12].…”
Section: Introductionmentioning
confidence: 99%